A-14 Competitiveness and Past Nondisclosure Decreases Future Concussion Reporting Intention Among Males in High-Contact Sports. (18th June 2020) - Doucette, M M; Wong, R E; Du Plessis, S; Garcia-Barrera, M
Abstract: Objective: With some variability, research indicates that a high percentage (20–60%) of athletes do not report post-concussion symptoms, despite having sufficient concussion knowledge. Our study examined whether competitiveness and past reporting predicted future reporting intention in males participating in high contact sports. Method: Participants included 92 male athletes (M = 19.35 years, SD = 4.35) recruited from a mid-sized Canadian city participating in high contact sports (American football, rugby, or hockey). Competitiveness was measured using the Sport Orientation Questionnaire. The Rosenbaum Concussion Knowledge and Attitudes Survey-Student Version was used to assess concussion knowledge and nondisclosure. Logistic regression was conducted to predict future intention of playing despite experiencing post-concussion symptoms. Age, knowledge, competitiveness, sport, and past history of concussion nondisclosure were included as predictors. Results: Age, sport, and concussion knowledge were not significant predictors. Competitiveness was a significant predictor for the model, such that higher competitiveness predicted less likelihood to report post-concussion symptoms. Our findings also suggest that athletes who have not disclosed a concussion in the past are more likely to have higher intention to continue to play with symptoms of a concussion in the future. Over half (54%) of the athletes reported past history of concussion nondisclosure. Conclusions: Interventions focusing on increasing general concussion knowledge are not adequate to prevent symptom nondisclosure. The results suggest that highly competitive athletes or athletes with a past history of nondisclosure are most vulnerable to future nondisclosure. These findings could help improve future interventions by targeting athletes at high-risk of concussion nondisclosure.